Analysis of deaths due to acquired immunodeficiency syndrome - Katia Barbosa Franco; Gilmara Holanda da Cunha; Maria Amanda Correia Lima; Dalila Augusto Peres; Marli Teresinha Gimeniz Galvão; Reângela Cintia Rodrigues de Oliveira Lima (Rev Rene)
Objective: to analyze the profile of the deaths of people with acquired immunodeficiency syndrome. Methods: a cross-sectional study was carried out with 106 medical records of people who died in an intensive care unit, obtaining sociodemographic and clinical variables. Analysis made using Pearson’s chi-square test, Fisher’s test and Mann-Whitney test. Results:most of the patients were male (80.2%), in the age group from 18 to 39 years, average age of 39.7 years, 81.6% dark-skinned, 60.4% were single and 62.5% unemployed. The proportion of patients who were unemployed (p=0.002) and who did not use antiretroviral therapy (p<0.001) were the ones that had the least regular health care. Conclusion: most of the patients in the study did not follow regular health care and did not use antiretroviral therapy.